Emigration and Rising Wages in Myanmar: Evidence from Mon State. Issue 5 (3rd May 2020) - Filipski, Mateusz; Lee, Hak Lim; Hein, Aung; Nischan, Ulrike
Abstract: Whether and how immigration affects labour markets is a hotly-debated and widely-studied topic. By contrast, the converse question of how emigration impacts labour markets in the source economy has remained largely understudied. In particular, whether outflows of labourers lead to higher wages in their home countries has only been addressed in a handful of studies. This paper contributes to filling this knowledge gap using data from Myanmar. We collected primary household data from rural Mon State, a southern state neighbouring Thailand. Analysis shows that over a quarter of the labour force is currently migrating for work. Relying on variation in local wages at the village level, regression estimates reveal a significant relationship between migration and wages of unskilled agricultural workers. We use measures of past migration as instrumental variables to further show that this relationship is likely causal. Rapidly rising wages in Myanmar carry deep consequences for the development trajectory of the country.